Numerical research of influence of laser radiation parameters on the formation of intermetallic phases from metal powders in selective laser melting technology; AIP Conference Proceedings; Vol. 1893 : High-Energy Processes in Condensed Matter (HEPCM 2017) - Agapovichev A. V. Anton Vasiljevich (2017, 2017)
Title screen